Market Share Perbankan Syariah Di Indonesia: Makro Ekonomi Dan Financial Performance: Market Share of Islamic Banking in Indonesia: Macroeconomics and Financial Performance - Amalia, Baiq Naili; Wardana, Guntur Kusuma (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2024)
This study aimed to know the influence of macroeconomic factors (inflation, Bi Rate) and Financial Performance (ROA, CAR, FDR) onthe market share of Islamic banking in Indonesia. This study is quantitative with an explanatory approach. The population in this study consisted of 14 Islamic Commercial Banks. The sample consisted of 6Islamic Commercial Banks registered with the Financial Services Authority (OJK) and Bank Indonesia. The sample was taken using a purposive sampling technique. The data analysis used panel data regression with Eviews 9. The results show that partially inflation, Bi Rate, FDR variables had a significant negative effect on the market share. ROA and CAR variables have no significant effect on the market share. In addition, simultaneously the variables of Inflation, Bi Rate, ROA, CAR, FDR have a significant effect on market share.